Vaccine escape, increased breakthrough and reinfection in infliximab-treated patients with IBD during the Omicron wave of the SARS-CoV-2 pandemic. Issue 2 (28th July 2022) - Kennedy, Nicholas A; Janjua, Malik; Chanchlani, Neil; Lin, Simeng; Bewshea, Claire; Nice, Rachel; McDonald, Timothy J; Auckland, Cressida; Harries, Lorna W; Davies, Merlin; Michell, Stephen; Kok, Klaartje B; et al.
Abstract : Objective: Antitumour necrosis factor (TNF) drugs impair serological responses following SARS-CoV-2 vaccination. We sought to assess if a third dose of a messenger RNA (mRNA)-based vaccine substantially boosted anti-SARS-CoV-2 antibody responses and protective immunity in infliximab-treated patients with IBD. Design: Third dose vaccine induced anti-SARS-CoV-2 spike (anti-S) receptor-binding domain (RBD) antibody responses, breakthrough SARS-CoV-2 infection, reinfection and persistent oropharyngeal carriage in patients with IBD treated with infliximab were compared with a reference cohort treated with vedolizumab from the impaCt of bioLogic therApy on saRs-cov-2 Infection and immuniTY (CLARITY) IBD study. Results: Geometric mean (SD) anti-S RBD antibody concentrations increased in both groups following a third dose of an mRNA-based vaccine. However, concentrations were lower in patients treated with infliximab than vedolizumab, irrespective of whether their first two primary vaccine doses were ChAdOx1 nCoV-19 (1856 U/mL (5.2) vs 10 728 U/mL (3.1), p<0.0001) or BNT162b2 vaccines (2164 U/mL (4.1) vs 15 116 U/mL (3.4), p<0.0001). However, no differences in anti-S RBD antibody concentrations were seen following third and fourth doses of an mRNA-based vaccine, irrespective of the combination of primary vaccinations received. Post-third dose, anti-S RBD antibody half-life estimates were shorter in infliximab-treated than vedolizumab-treated patients (37.0 days (95% CI 35.6 to 38.6) vs 52.0 days (95% CI 49.0 to 55.4), p<0.0001). Compared with vedolizumab-treated, infliximab-treated patients were more likely to experience SARS-CoV-2 breakthrough infection (HR 2.23 (95% CI 1.46 to 3.38), p=0.00018) and reinfection (HR 2.10 (95% CI 1.31 to 3.35), p=0.0019), but this effect was uncoupled from third vaccine dose anti-S RBD antibody concentrations. Reinfection occurred predominantly during the Omicron wave and was predicted by SARS-CoV-2 antinucleocapsid concentrations after the initial infection. We did not observe persistent oropharyngeal carriage of SARS-CoV-2. Hospitalisations and deaths were uncommon in both groups. Conclusions: Following a third dose of an mRNA-based vaccine, infliximab was associated with attenuated serological responses and more SARS-CoV-2 breakthrough infection and reinfection which were not predicted by the magnitude of anti-S RBD responses, indicative of vaccine escape by the Omicron variant. Trial registration number: ISRCTN45176516 .